Innovative Flint Hills cattle ranchers' decision-making regarding herd productivity and rangeland management practices: a qualitative study - Baughman, Madison Elizabeth (Kansas State University, 2023)
Innovative rangeland management practices in the beef industry improve ecosystem health while benefiting herd productivity of a cattle ranching operation. Despite the proven benefits, some ranchers choose not to adopt these practices. The purpose of this study was to better understand Flint Hills, Kansas ranchers’ decision making in balancing herd productivity and rangeland health. The Flint Hills region is the largest remaining tract of native tallgrass prairie in the U.S. and has a long history as grazing land for cattle. Two conceptual frameworks were used to guide this study: Diffusion of Innovations Theory and Good Farmer Theory. Diffusion of Innovations Theory describes how innovations are adopted through specific populations over time. Adopter categories are innovators, early adopters, early majority, late majority, and laggards. Attributes of innovations are relative advantage, compatibility, complexity, trialability and observability. Good Farmer Theory analyzes the lenses through which producers view themselves and others as “good farmers.” Twelve semi-structured interviews were conducted with cattle ranchers in the Flint Hills region of Kansas who are perceived as innovators or early adopters in their rangeland management practices. Interview questions related to how producers view herd productivity and rangeland management practices on their operations; specific rangeland management practices they are currently utilizing or considering trying next; and the social constructs driving perceptions of good rangeland management in their communities. Results show the innovative producers in this study utilize systems thinking in the context of economics and ecosystem, ecosystem and cattle, and ecosystem preservation as a necessity. Producers have an adaptive management style, utilizing visual evidence, regular adjustments, and input sensitivity, to make decisions regarding rangeland management on their operations. Flint Hills producer interviewees’ perceived benefits and barriers to current and potential rangeland management practices impact implementation of rangeland management practices. In addition, producer decision-making is impacted by multiple spheres of influence, including peer pressure, selective influence by ranchers and experts they respect, and shared stories and information gathering. Visual indicators and community norms are used by producers in this study to determine “good” rangeland management standards. Producers also use visual evidence and shared stories and information gathering to make informed decisions on how to manage their individual operations. Future research in this topic area should explore how early majority, late majority and laggard Flint Hills producers perceive and make decisions regarding rangeland management practices on their operations. In addition, further research should dive into how producer decision making is impacted by influential organizations and Extension events. This study confirmed and expanded on how producer perceptions of rangeland management practices impact implementation on their own operations.
Keywords: Producer decision-making; Herd productivity; Rangeland management practices; Social contexts